A Novel Energy Recovery System for Parallel Hybrid Hydraulic Excavator - Wei Li; Baoyu Cao; Zhencai Zhu; Guoan Chen (The Scientific World Journal)
Hydraulic excavator energy saving is important to relieve source shortage and protect environment. This paper mainly discusses the energy saving for the hybrid hydraulic excavator. By analyzing the excess energy of three hydraulic cylinders in the conventional hydraulic excavator, a new boom potential energy recovery system is proposed. The mathematical models of the main components including boom cylinder, hydraulic motor, and hydraulic accumulator are built. The natural frequency of the proposed energy recovery system is calculated based on the mathematical models. Meanwhile, the simulation models of the proposed system and a conventional energy recovery system are built by AMESim software. The results show that the proposed system is more effective than the conventional energy saving system. At last, the main components of the proposed energy recovery system including accumulator and hydraulic motor are analyzed for improving the energy recovery efficiency. The measures to improve the energy recovery efficiency of the proposed system are presented.